ENERGY EFFICIENCY AWARENESS AND PRACTICES BASED ON ISLAMIC PERSPECTIVES - Muszaffarsham, Nurul Hadirah; Kandar, Mohd Zin; Mohd Husini, Elina (PLANNING MALAYSIA, 2022)
Currently, the main environmental concerns encountered by most countries are energy and its consumption. A green lifestyle and energy efficiency (EE) could reduce daily energy consumption. Nevertheless, low awareness and knowledge of EE prevent proper green lifestyle practices to save energy and the environment. Thus, the study aims to examine building occupants’ EE and energy conservation awareness and practices based on Islamic perspectives. The study objectives are to examine the level of EE awareness and practices among Malaysian building occupants and incorporate the potential of Islamic teachings from al-Quran concerning energy consumption and conservation in the EE awareness campaigns. The study used the qualitative research method, which involved a literature review, observation, and narrative study. As a result, the significant relevance of EE awareness and practices along with Islamic teachings is explained further in this study. Moreover, instilling knowledge, creating awareness and encouraging occupants to implement EE practices, which consequently reduce energy demand and energy consumption, hence, mitigating the detrimental environmental impacts. The study is crucial in raising public awareness of the Islamic perspectives linked with energy conservation and provides a framework for future development plans that embody EE elements aligned with Islamic teachings.